Pengaruh NPL, LDR, dan CAR padaROA Perusahaan Perbankan yang Terdaftar di BEI Tahun 2014-2016 - Dewi, Putu Intan Trisna; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2018)
Banking plays an important role in influencing economic activity. Banking is required to gain profit so as to compete in order to maintain its survival. The profit is used to pay for all types of operational costs. This research was conducted in Banking Companies Listed in Indonesia Stock Exchange Period Year 2014 - 2016. The number of samples is 20 banks, with the method of purposive sampling technique. Data collection is done by observation or observation. The analysis technique used is multiple linear regression analysis. Based on the result of research, it is known that non performing loan has negative effect on return on asset, loan to deposit ratio has positive effect on return on asset, and capital adequacy ratio has negative effect on return on asset. Keywords : Non Performing Loan, Loan to Deposit Ratio, Capital Adequacy Ratio, Return On Assets.